Development of a High-throughput Agar Colony Formation Assay to Identify Drug Candidates against Medulloblastoma - Mohammed Sedeeq; Ahmed Maklad; Nuri Gueven; Iman Azimi (MDPI AG, 2020)
Medulloblastoma (MB) is the most common malignant childhood brain cancer. High-risk MB tumours have a high incidence of metastasis and result in poor patient survival. Drug screens, commonly used to identify potential novel therapeutic agents against MB, focus on 2D cell proliferation and viability assays given that these assays are easily adaptable to high-throughput regimes. However, 2D models fail to address invasive characteristics that are crucial to MB metastasis and are thus not representative of tumour growth in vivo. In this study, we developed a 3D 384-well agar colony formation assay using MB cells of molecular subgroup 3 that is associated with the highest level of metastasis. Two fluorescence substrates, resazurin and glycyl-phenylalanyl-aminofluorocoumarin (GF-AFC) that measure cell viability via distinct mechanisms were used to assess the growth of MB cells in the agar matrix. The assay was optimised for seeding density, growth period, substrate incubation time and homogeneity of the fluorescent signals within individual wells. Our data demonstrate the feasibility to multiplex the two fluorescent substrates without detectable signal interference. This assay was validated by assessing the concentration-dependent effect of two commonly used chemotherapeutic agents clinically used for MB treatment, vincristine and lomustine. Subsequently, a panel of plasma membrane calcium channel modulators was screened for their effect on the 3D growth of D341 MB cells, which identified modulators of T-type voltage gated and ORAI calcium channels as selective growth modulators. Overall, this 3D assay provides a reproducible, time and cost-effective assay for high-throughput screening to identify potential drugs against MB.